Causality Analysis to the Abnormal Subcortical–Cortical Connections in Idiopathic-Generalized Epilepsy - Qin, Yun; Li, Sipei; Yao, Dezhong; Luo, Cheng (Frontiers in Neuroscience, 2022)
Idiopathic generalized epilepsy (IGE) was characterized by 3-6Hz generalized spike-wave discharges, and extensive altered interactions in subcortical-cortical circuit. However, the dynamics and the causal relationship among these interactions were less studied. Using resting-state fMRI data, the abnormal connections in subcortical-cortical pathway in IGE were examined. Then, we proposed a novel method of granger causal analysis based on the dynamic functional connectivity, and the predictive effects among these abnormal connections were calculated. The results showed that thalamus, precuneus were key regions representing abnormal functional network connectivity in subcortical-cortical circuit. Moreover, the connectivity between precuneus and adjacent regions had causal effect on the widespread dysfunction of thalamocortical circuit. In addition, the connection between the striatum and thalamus indicated the modulation role on the cortical connection in epilepsy. These results described the causality of the widespread abnormality of subcortical-cortical circuit in IGE in terms of the dynamics of functional connections, which provided additional evidence for understanding the potential modulation pattern of the abnormal epileptic pathway.